Digital business and e-commerce management - Chaffey, Dave (Pearson, 2024)
This book offers a comprehensive guide to managing digital business and e-commerce. It covers key strategies for digital transformation, online marketing, customer engagement, and technology use in business. With real-world case studies and updated content on AI and digital platforms, it is an essential resource for understanding how to succeed in today's digital economy.